A review of literature on evaluating the scientific, social and political impact of social sciences and humanities research. Issue 4 (18th July 2017) - Reale, Emanuela; Avramov, Dragana; Canhial, Kubra; Donovan, Claire; Flecha, Ramon; Holm, Poul; Larkin, Charles; Lepori, Benedetto; Mosoni-Fried, Judith; Oliver, Esther; Primeri, Emilia; Puigvert, Lidia; et al.
Abstract: Recently, the need to contribute to the evaluation of the scientific, social, and political impact of Social Sciences and Humanities (SSH) research has become a demand of policy makers and society. The international scientific community has made significant advances that have transformed the impact of evaluation landscape. This article reviews the existing scientific knowledge on evaluation tools and techniques that are applied to assess the scientific impact of SSH research; the changing structure of social and political impacts of SSH research is investigated based on an overarching research question: to what extent do scholars attempt to apply methods, instruments, and approaches that take into account the distinctive features of SSH? The review also includes examples of European Union (EU) projects that demonstrate these impacts. This article culminates in a discussion of the development of the assessment of different impacts and identifies limitations, and areas and topics to explore in the future.